Dari Gerak ke Suara: Interaksi Gestur, Bunyi, dan Teknologi dalam Seni Pertunjukan - Aristadewi, Ni Putu (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study discusses the transformation of the body's role in contemporary performing arts through the interaction between gesture, sound, and technology. Starting from a paradigm shift in musical understanding, this study highlights how the body is no longer just a medium of expression, but also functions as an active controller in sound production, especially in the context of digital technology-based performances. Research methods: Using a qualitative descriptive-analytical approach and the theoretical framework of embodied music cognition and sound-action awareness, this study analyzes a number of video documentations of performances—from Balinese gamelan to the use of digital instruments such as theremin, sensory gloves, and ROLI Blocks. Results and discussion: The analysis shows that the body plays a central role in creating and modulating musical experiences in real time through gestures that are directly connected to the sound system. Implication: These findings reinforce the view that the integration of the body and technology opens up new pathways in performing arts practices and expands the traditional boundaries between instruments, performers, and voices.